Enhancing the quality of industrial wastewater by using natural membranes - Hemalatha A.; Hussain Muhamed; Venkatesh M.; Bhargavi Y. Krishna; Misra Neeti (E3S Web of Conferences, 2024)
The entire world is facing a water crisis due to population growth as well as global warming. The maximum quantity of water is utilized for industrial and agricultural purposes. Based on these causes, each nation focuses on wastewater recycling techniques. Researchers have innovated a myriad of wastewater treatment methods, along with natural and artificial methods. Apart from this, cost plays a major role in the massive waste water treatment process. By considering the factor generally, the water treatment projects effectively concentrated on assigning natural and easily available materials. This research focuses on industrial wastewater treatment. A water purification process is meant to remove or reduce contaminants in water until it is safe to use. In addition to increasing the odour and flavour of the water, the purification procedures used in this experiment will help to eliminate pollutants and give it a cleaner appearance. This procedure employs natural membranes such as coconut coir, charcoal, and fine sand. This strategy is simple and preferred by anyone owing to the low cost and local availability of the required supplies. On observing the experimental test results, the natural membrane materials provide an effective performance change in the properties of waste water within acceptable limits.